Pengaruh Masa Perikatan Audit, Rotasi Kap, Ukuran Perusahaan Klien, Ukuran Kap, Dan Fee Audit Terhadap Kualitas Audit(Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2011-2013) - Hadi, Rama San Cahya, Drs. Agus Endro Suwarno, M.Si (2017)
Purpose of the research is to know and analyze effect of tenure, rotation of public accounting office, size of client company, size of public accounting office, fee audit on audit quality in manufacturing company registered in Indonesian Exchange of 2011-2013. Population of the research is 152 manufacturing companies registered in Indonesian Exchange of 2011-2013. Sample was taken by using purposive sampling, namely sampling with certain consideration. The consideration were, among the others, (1) Manufacturing companies registered in Indonesian Exchange must have financial statements and annual reports of 2011-2013, so that annual information of the companies can be known; (2) the companies provides information that will be used by researcher in finding values of variables used; (3) the companies provides financial statements with rupiah currency; (4) companies with the end of accountancy period of 31 December for period of 2011-2013; (5) the companies must have audited financial statements of 2011-2013. Based on the criteria, data sample of 32 manufacturing companies for period of 3 years were obtained, so that sample was 102 data. Data source was financial statements and annual report acquired by accessing www.idx.co.id. The data was analyzed by using descriptive analysis and logistic regression analysis. Results of logistic regression obtained results as follow: (1) Tenure of audit, rotation of public accounting office and size of client company had no significant effect on audit quality; (2) Size of public accounting office and fee audit had significant effect on audit quality.